GR-MHD disk winds and jets from black holes and resistive accretion disks - Vourellis, Christos; Fendt, Christian; Qian, Qian (The astrophysical journal, 2019)
We perform GR-MHD simulations of outﬂow launching from thin accretion disks. As in the nonrelativistic case, resistivity is essential for the mass loading of the disk wind. We implemented resistivity in the ideal GR-MHD code HARM3D, extending previous works for larger physical grids, higher spatial resolution, and longer simulation time. We consider an initially thin, resistive disk orbiting the black hole, threaded by a large-scale magnetic ﬂux. As the system evolves, outﬂows are launched from the black hole magnetosphere and the disk surface. We mainly focus on disk outﬂows, investigating their MHD structure and energy output in comparison with the Poyntingdominated black hole jet. The disk wind encloses two components—a fast component dominated by the toroidal magnetic ﬁeld and a slower component dominated by the poloidal ﬁeld. The disk wind transitions from sub- to super-Alfvénic speed, reaching velocities ;0.1c. We provide parameter studies varying spin parameter and resistivity level and measure the respective mass and energy ﬂuxes. A higher spin strengthens the Bf-dominated disk wind along the inner jet. We disentangle a critical resistivity level that leads to a maximum matter and energy output for both, resulting from the interplay between reconnection and diffusion, which in combination govern the magnetic ﬂux and the mass loading. For counterrotating black holes the outﬂow structure shows a magnetic ﬁeld reversal. We estimate the opacity of the innermost accretion stream and the outﬂow structure around it. This stream may be critically opaque for a lensed signal, while the axial jet funnel remains optically thin.